PEMBERDAYAAN BERBASIS REMAJA MASJID AL-MUJAHIDIN DESA CIATER - Neng Chery Sukma Ayu; Syamsuddin RS; Rohmanur Aziz (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2021)
In the era of globalization, teenagers are busy with technological developments where social media has much influence on the lives of teenagers at this time. The influence of technological advances impacts cultural change, and today's young people imitate many foreign cultures. This will continue to shape life in the future. If juvenile delinquency continues, then public trust in adolescents will decrease. This study aimed to find out about the program, implementation, and results of youth empowerment. The research method used in this study is a descriptive qualitative approach to provide an overview through observational data, interviews, and documentation. The results showed that IRMAS in Ciater Village carried out youth empowerment through the Ramadhan santri boarding school program, lanterns for village children, and creative workshops. The implementation process is through planning, implementation, monitoring, and evaluation. The results of empowerment can increase understanding and channel the potential in members, the emergence of member participation in empowerment programs, and youth involvement in the organizational structure of the Ciater Village government.